Cross-platform interface LABVIEW for microprocessor systems - Protsenko, D. P.; Shevchuk, Yu. V.; Dvornitskyi, R. V. (Visnyk of Vinnytsia Politechnical Institute, 2014)
Development and approbation of cross-platform interface of LabVIEW for microprocessor systems are conducted, that provides the dynamic transmission of necessary amount of data without influence on the main program of functioning of microprocessor system that gives an opportunity of integration of interface of connection with LabVIEW in already existent microprocessor system.